Health-related quality of life of adolescents in the context of selected somatic development indices - Krawczyńska, Jadwiga; Łukawska, Paulina (Medical Studies/Studia Medyczne, 2016)
Introduction: The measurement of health-related quality of life (HRQOL) is nowadays one of the most important methods of self-assessment of health, which makes it possible to detect abnormalities in physical, mental, and social functioning. The weight-growth body mass index (BMI), which determines the degree of nourishment, is essential in the evaluation of the somatic development. Aim of the research: The assessment of HRQOL depending on the weight-growth rate and gender of the pupils. Material and methods : The study involved 588 pupils aged 16–18 years. The authors applied in the study the methods of survey and analysis of pupils’ health records. The KIDSCREEN-52, designed to test the health-related quality of life, was the research tool. Results : The BMI analysis showed a clear advantage of pupils with normal weight. Among boys the percentage of individuals suspected of overweight and obesity was higher, whereas among girls the higher percentage involved individuals with body weight deficit. The results of HRQOL show that obese boys evaluated the highest their financial resources, autonomy, and relationships with parents. The pupils with body weight deficit evaluated the lowest their self-image. The overweight boys evaluated their mental wellbeing the lowest in comparison to others, and the highest their self-image. Overweight girls evaluated the lowest their self-image, emotions, and the school environment. The girls with body weight deficit evaluated the highest their relations with parents, and the lowest their autonomy. Conclusions : The values of the BMI among the surveyed pupils show an explicit prevalence of individuals with normal body mass. The results of the pupils with eating disorders were lower in all categories of HRQOL. No dependence was confirmed between the BMIs of pupils and the results of the KIDSCREEN-52 questionnaire in any of the assessed category of HRQOL (p > 0.05).